PHOTO SELFIE AS WOMEN'S EXPRESSION OF FEMININITY - Mecca, Ali (Capture : Jurnal Seni Media Rekam, 2019)
In selfie photos, women are no longer positioned as objects from photographers, but rather act as subjects who take pictures as well as the subject being photographed. Women in this context become more aware of the values of femininity that have been attached to their bodies. This study aims to identify expressions of femininity represented in selfie. The method used in this study is audience research. The results of the study show two things. First, the physical beauty represented by selfie includes the brightness of facial skin, thin cheeks, and the reddish of red lips. Second, femininity as an expression of their body being identified again into three aspects, namely, women as objects, women as subjects, and women as both of subjects and objects.